Atherosclerosis Treatment with Stimuli‐Responsive Nanoagents: Recent Advances and Future Perspectives. Issue 11 (3rd April 2019) - Maruf, Ali; Wang, Yi; Yin, Tieyin; Huang, Junli; Wang, Nan; Durkan, Colm; Tan, Youhua; Wu, Wei; Wang, Guixue
Abstract: Atherosclerosis is the root of approximately one‐third of global mortalities. Nanotechnology exhibits splendid prospects to combat atherosclerosis at the molecular level by engineering smart nanoagents with versatile functionalizations. Significant advances in nanoengineering enable nanoagents to autonomously navigate in the bloodstream, escape from biological barriers, and assemble with their nanocohort at the targeted lesion. The assembly of nanoagents with endogenous and exogenous stimuli breaks down their shells, facilitates intracellular delivery, releases their cargo to kill the corrupt cells, and gives imaging reports. All these improvements pave the way toward personalized medicine for atherosclerosis. This review systematically summarizes the recent advances in stimuli‐responsive nanoagents for atherosclerosis management and its progress in clinical trials. Abstract : Can smart nanoagents combat atherosclerosis? Endogenous stimuli (reactive oxygen species, enzymes, pH, and shear stress) that are present in atherosclerosis and exogenous stimuli (light, ultrasound, and magnetic field) provide a magnificent opportunity as fine‐tuning tools to dismantle stimuli‐responsive nanoagents, release their cargo, and give imaging reports, thereby providing theranostic hallmarks to synergistically combat atherosclerosis.